PARTICLE SWARM OPTIMIZATION AND COMBINATORIAL AUCTION BASED MODELING OF THE MULTI-UNIT SPECTRUM ALLOCATION (BIDDING) PROBLEM - Jhankal, Anuj Kumar; Pathak, Vishwambhar (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
Paper has been withdraw.